Introducing cross-cultural education in palliative care: focus groups with experts on practical strategies - Imane Semlali; Emmanuel Tamches; Pascal Singy; Orest Weber (BMC Palliative Care, 2020)
Abstract Background The linguistic and cultural diversity found in European societies creates specific challenges to palliative care clinicians. Patients’ heterogeneous habits, beliefs and social situations, and in many cases language barriers, add complexity to clinicians’ work. Cross-cultural teaching helps palliative care specialists deal with issues that arise from such diversity. This study aimed to provide interested educators and decision makers with ideas for how to implement cross-cultural training in palliative care. Methods We conducted four focus groups in French- and Italian-speaking Switzerland. All groups consisted of a mix of experts in palliative care and/or cross-cultural teaching. The interdisciplinary research team submitted the data for thematic content analysis. Results Focus-group participants saw a clear need for courses addressing cross-cultural issues in end-of-life care, including in medical disciplines outside of palliative care (e.g. geriatrics, oncology, intensive care). We found that these courses should be embedded in existing training offerings and should appear at all stages of curricula for end-of-life specialists. Two trends emerged related to course content. One focuses on clinicians’ acquisition of cultural expertise and tools allowing them to deal with complex situations on their own; the other stresses the importance of clinicians’ reflections and learning to collaborate with other professionals in complex situations. These trends evoke recent debates in the literature: the quest for expertise and tools is related to traditional twentieth century work on cross-cultural competence, whereas reflection and collaboration are central to more recent research that promotes cultural sensitivity and humility in clinicians. Conclusion This study offers new insights into cross-cultural courses in palliative and end-of-life care. Basic knowledge on culture in medicine, variable practices related to death and dying, communication techniques, self-reflection on cultural references and aptitude for interprofessional collaboration are central to preparing clinicians in end-of-life settings to work with linguistically and culturally diverse patients.